FACTORS AFFECTING THE CUSTOMER LOYALTY OF SHARIA RURAL BANK - Irwan Maulana; Yuswar Zainul Basri; Tatik Mariyati (Univeristas Islam Bandung, 2022)
The purpose of this research to analyze and prove empirically factors affecting the customer loyalty of sharia rural bank in Banten Province with satisfaction as an intervening variable. This research is a quantitative research using structural equation modeling (SEM). A total of 677 respondents were people who used BPRS services and products obtained by purposive random sampling questionnaire distribution of 58 questions to eight BPRS in Banten Province. The result of this research indicates that the BPRS service factor is not the main measure of forming customer loyalty, but through religiosity and knowledge variables, the higher one’s religiosity, make the tendency higher to use an BPRS services. The knowledge factor is the most powerful factor forming customer loyalty. Increasingly know the importance of Islamic principles for daily muamalah, make the tendency higher to use an BPRS services. The implications of this study show that the BPRS needs to build satisfaction gradually to realize loyal customers, the services provided by the BPRS must be different from those offered by commercial banks like pick up service is applicable for all customers and not just focus on priority customers only, or the BPRS needs to cooperate with commercial banks to get facilities that can accommodate customer needs. Secondly, BPRS need to hold Islamic financial education programs to the public through literacy and financial inclusion regularly, measurable and suatainable in order to improve the BPRS marketshare